Leukocytes infiltrate the myometrium during human parturition: further evidence that labour is an inflammatory process - Andrew J. Thomson; Joan F. Telfer; Anne Young; S Campbell; Colin J.R. Stewart; Iain Cameron; Ian A. Greer; Jane E. Norman (1999)
Inflammatory mediators in the cervix, placenta and fetal membranes play a crucial role in human parturition. The aim of this study was to determine whether the upper and lower segments of the myometrium are infiltrated by inflammatory cells during pregnancy and parturition. Myometrial biopsies were obtained from non-pregnant women, and pregnant women at term before and after the onset of spontaneous labour. Subpopulations of inflammatory cells were identified using immunocytochemistry. The intercellular adhesion molecules, 1 and 2, platelet endothelial cell adhesion molecule, vascular cell adhesion molecule and E-selectin were immunolocalized to investigate their involvement in leukocyte accumulation. Histological analysis demonstrated that inflammatory cells, predominantly neutrophils and macrophages, infiltrate human myometrium during spontaneous labour at term. The infiltrate is predominant in the lower uterine segment but is also present in the upper segment. Increased expression of E-selectin was found on the vascular endothelium of biopsies obtained during labour, suggesting a role for this molecule in the accumulation of leukocytes. These results suggest that inflammatory cell infiltration is part of the physiological mechanisms that occur in the myometrium during parturition. Further understanding of this process may suggest new strategies aimed at preventing preterm delivery.